Law Enforcement Through Judicial Institutions Within The Indonesian Constitutional System - Minanoer Rachman (Universitas Airlangga, 2026)
Fundamentally, the execution of a Court Decision that has attained permanent legal force (inkracht van gewijsde) constitutes the final stage in the sequence of litigation proceedings within judicial institutions. However, decisions eligible for immediate execution (uitvoerbaar bij voorraad), as stipulated under Article 180 paragraph (1) of the Herzien Inlandsch Reglement (HIR), may be enforced prematurely. This applies even if the decision has not yet become final and binding due to the losing party pursuing legal remedies such as verzet (opposition), appeal, or cassation. In practice, however, losing parties often demonstrate a lack of voluntary compliance in fulfilling the obligations dictated by a Court Decision. Consequently, intervention from an external authority is necessitated; in this context, the court is legally empowered to